Erick Thohir's Approach to Public Relations Politics in Building Image on Instagram Social Media - Faisal Maarif; Harmonis (Institute of Computer Science (IOCS), 2022)
The development of social media into a platform that is widely accessed by the public has made many public or political figures pay attention to it. One of them is Erick Thohir, who plays quite intensely on Instagram social media with various content uploaded every day. This allows it to become a political public relations strategy in building its image in society. This study aims to determine the political Public Relations approach used by Erick Thohir through social media Instagram. The method used in this research is descriptive qualitative by tracing and exploring the contents on Instagram. The findings of this research include, Erick Thohir uses the Political Relations approach with the Public.